ABOUT THE SPIRITUAL ARTISTIC WORKS OF ABDULLA AWLANI - Mustafayev J.Sh.; Bakhriddinova Rukhshona Bakhodirovna (Journal of new century innovations, 2024)
Annotation: The role and importance of pedagogical scientific heritage of Abdulla Avloni, one of the exponents of the Enlightenment movement, in pedagogical moral education in the process of organizing the educational system is highlighted in the article. Abdulla Awlani's views on many works on education and their influence on the education of the young generation in the current era of globalization were studied.